Plant Values, Reap Values Character: Career Scouting in Schools Border Facing the Era 5.0 - Muslimah Muslimah; Khairil Anwar; Nor Faridatunnisa; Mustafa Mustafa; Lida Rofikoh (Universitas Wahid Hasyim Semarang, 2025)
This article discusses the role of scout activities, namely Pramuka at SDN 14 Manis Mata and Hizbul Wathan at SDIT Muhammadiyah Sukamara, in shaping the character of elementary school students in the border area of West Kalimantan and Central Kalimantan. The study focuses on two schools, using a qualitative-descriptive approach. Data was collected through observation, interviews, and documentation of scout activities at each school. Findings indicate that planning is conducted participatively, involving various stakeholders, reflecting the principles of consultation and program flexibility. In terms of organization, both schools assign instructors based on their competencies, either through external trainers or certified internal teachers. The implementation of activities featured the integration of religious culture into routine activities interspersed with spiritual activities. Activity evaluations were carried out systematically and used for continuous program development. Scout activities were proven to strengthen students' character in terms of discipline, responsibility, independence, spirituality, and social awareness. This study concludes that scout activity management based on religious values, local culture, and a holistic approach can address the challenges of character development in the Society 5.0 era, particularly in 3T regions. Keywords: Hizbul Wathan, Character, Scouting, Border School